Inhibition of ERK MAPK suppresses IL-23- and IL-1-driven IL-17 production and attenuates autoimmune disease. - LAVELLE, EDWARD; MILLS, KINGSTON; LALOR, STEPHEN (My University, 2009)
IL-17 producing CD4+ T (Th17) cells are pathogenic in many autoimmune diseases. The induction and expansion of Th17 cells is directed by cytokines, including IL-23 and IL-1?, produced by innate immune cells through activation of pathogen recognition receptors (PRRs). The NF?B and interferon regulatory factor (IRF) families of transcriptional factors mediate IL-12 production; however, distinct signalling pathways appear to be required for IL- 23 production. Here we show that inhibition of ERK MAP kinase suppressed IL-23 and IL-1? production by dendritic cells (DC) stimulated with TLR or dectin-1 agonists, but did not affect IL-12p70 production. Furthermore, an ERK inhibitor suppressed the ability of antigen-pulsed TLR-activated DC to induce antigen-specific Th17 cells in vivo, but interestingly also inhibited the induction of Th1 cells. Treatment with an ERK inhibitor attenuated experimental autoimmune encephalomyelitis (EAE), when administered either at the induction phase of acute EAE or during remission in the relapsing-remitting EAE model. This was associated with significant suppression of autoantigen-specific Th17 and Th1 responses. The suppressive effect of the ERK inhibitor on attenuation of EAE was reversed by administration of IL-1? and IL-23. Our findings suggest that ERK MAP kinase plays a critical and hitherto undescribed role in activating innate production of IL-23 and IL-1?, which promote pathogenic T cell responses, and therefore represents an important target for therapeutic intervention against autoimmune diseases.
PUBLISHED
PMID: 19570828
Keywords: suppression; autoimmunity; EAE; ERK MAPK; Immunology, Inflammation & Infection